Commiphora namibensis (Burseraceae), a new species from Angola - Swanepoel, Wessel (Phytotaxa, 2014)
Commiphora namibensis Swanepoel, described here as a new species, is known only from the Kaokoveld Centre of Endemism, southwestern Angola. It appears to be closely related to C. virgata Engl. Diagnostic morphological characters of C. namibensis include the mostly spinescent lateral branches and branchlets, trifoliolate leaves, rarely with a few simple ones also present, the leaflets which are shiny adaxially and a laterally slightly compressed putamen with a yellow pseudo-aril. Illustrations of the plant and a distribution map are provided. Mainly confined to near the coast, the new species is widespread but uncommon between Namibe and Santa Maria.